Detection of lipoprotein(a)- cholesterol expression in Bangladeshi adults with dyslipidemia - Puja Biswas; Fakir Md Yunus; Tareq Hossan; Sohel Ahmed (Intelektual Pustaka Media Utama, 2019)
Lipoprotein(a)-cholesterol (Lp(a)-C), a low-density lipoprotein (LDL)-like particle is considered as a risk factor for cardiovascular diseases (CVDs). We aimed to investigate the association of Lp(a)-C expression with dyslipidemia among the Bangladeshi population and assess the relationship with cardiovascular risks. In this cross-sectional comparative study, a total of 180 urban males and females between ages 19-65 years were included who were enrolled in a hospital setting of Bangladesh. Participants were selected based on their total cholesterol (TC) level≥200 mg/dl, high density lipoprotein (HDL)-C<40 mg/dl, LDL-C≥140 mg/dl, and triacylglycerol (TG)≥150 mg/dl regardless of race, religion and socioeconomic status. Venous blood was collected from all participants and analyzed. Further, participants’ socio-demographics and body mass index (BMI) were collected. Expression of Lp(a)-C was detected in 22.86% patients with desirable levels (<14 mg/dL) of serum Lp(a)-C. This study suggests that the prevalence of hyperlipidemia and hypertriglyceridemia is high in the Bangladeshi population. Males were found to have lower HDL-C and higher TG than females. and, similar to other ethnic groups, a negative correlation between BMI and HDL-C was found in this population. In addition, Lp(a)-C had a positive correlation with TG which may recommend routine clinical investigation of Lp(a)-C as a biomarker for CVD risk.